2020
DOI: 10.1161/jaha.120.018219
|View full text |Cite
|
Sign up to set email alerts
|

PAPP‐A2 and Inhibin A as Novel Predictors for Pregnancy Complications in Women With Suspected or Confirmed Preeclampsia

Abstract: Background We aimed to evaluate the value of inhibin A and PAPP‐A2 (pregnancy‐associated plasma protein‐A2) as novel biomarkers in the prediction of preeclampsia‐related complications and how they compare with angiogenic biomarkers. Methods and Results Making use of a secondary analysis of a prospective, multicenter, observational study, intended to evaluate the usefulness of sFlt‐1 (soluble Fms‐like tyrosine kinase‐1)/PlGF (placental growth factor) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…Similarly, the expression of SDC1, NPPB (natriuretic peptide B), GDF15 (growth differentiation factor 15), and ADAMTS6 (ADAM metallopeptidase with thrombospondin type 1 motif 6) all had a lower expression in our experimental exposures, and all are lower in preeclampsia ( Junus et al, 2014 ; Chen et al, 2016 ; Gandley et al, 2016 ; Jiang et al, 2020 ). In contrast, our data are inconsistent with respect to the expression of PAPPA2, a regulator of trophoblast invasion and migration, or MNDA (myeloid cell nuclear differentiation antigen), which exhibited a lower expression level in our paradigms but is elevated in placentas from women with preeclampsia ( Wagner et al, 2011 ; Kolialexi et al, 2017 ; Neuman et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 97%
“…Similarly, the expression of SDC1, NPPB (natriuretic peptide B), GDF15 (growth differentiation factor 15), and ADAMTS6 (ADAM metallopeptidase with thrombospondin type 1 motif 6) all had a lower expression in our experimental exposures, and all are lower in preeclampsia ( Junus et al, 2014 ; Chen et al, 2016 ; Gandley et al, 2016 ; Jiang et al, 2020 ). In contrast, our data are inconsistent with respect to the expression of PAPPA2, a regulator of trophoblast invasion and migration, or MNDA (myeloid cell nuclear differentiation antigen), which exhibited a lower expression level in our paradigms but is elevated in placentas from women with preeclampsia ( Wagner et al, 2011 ; Kolialexi et al, 2017 ; Neuman et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 97%
“…The high correlation was found for increased Inhibin-A and sflt-1 / PlGF ratio for PE and PE+FGR, but not for FGR alone, whereas the decrease of PlGF yielded high correlations with each of the three complications. Hence, we are expanding the conclusions of Neuman et al [42].…”
Section: Interpretation Of Results and Comparison With Findings Of Prmentioning
confidence: 59%
“…Inhibin-A is a glycoprotein hormone that is abundantly expressed in the placenta and its levels in both the placental and circulating maternal levels are increased in cases of PE, and the increase is apparent from the second trimester of pregnancy [23,26,27]. Inhibin-A was initially identified as a second trimester marker of chromosomal abnormalities [37] and was subsequently reported as a second and third trimester marker of PE [37][38][39][40][41][42]. We found that Inhibin-A level is considerably higher in early than late PE the magnitude of increase was greater in PE alone rather than PE+FGR or FGR alone.…”
Section: Interpretation Of Results and Comparison With Findings Of Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibin-A is a glycoprotein hormone that is abundantly expressed in the placenta, and its levels in both the placental and circulating maternal levels are increased in cases of PE, and the increase is apparent from the second trimester of pregnancy [23,26,27]. Inhibin-A was initially identified as a second trimester marker of chromosomal abnormalities [37] and was subsequently reported as a second and third trimester marker of PE [37][38][39][40][41][42]. We found that the Inhibin-A level is considerably higher in early than late PE; the magnitude of increase was greater in PE alone rather than PE+FGR or FGR alone.…”
Section: Interpretation Of Results and Comparison With Findings Of Previous Studiesmentioning
confidence: 99%